Students’ motivation to learn English: the importance of external influence on the ideal L2 self - Ishida, Ayame; Manalo, Emmanuel; Sekiyama, Takashi (Frontiers in Education, 2024)
The ideal second/foreign language (L2) self, a concept in second-language acquisition theory, is a learner's future vision about their language ability. Research on the ideal L2 self is important for finding ways to improve motivation for learning a new language, foreign language teaching strategies, and personalization of instruction for individuals with different backgrounds and aspirations. The present study aimed to better understand the factors that might influence the ideal L2 self among Japanese elementary school students. While there have been numerous studies about the ideal L2 self in English language learning, few have focused on elementary school students' motivation to learn English. Methods: Data were collected from 225 4th-and 6th-grade elementary school students in Japan. The data were analyzed by performing t-tests and a hierarchical linear regression to understand the relationships between the pertinent variables and the ideal L2 self. Results: The analysis results revealed three characteristics of the relationship between elementary school students' English language skills and their ideal L2 selves. First, the results of the t-test suggested that international travel and English cram school experiences were differentiating factors for the ideal L2 self, suggesting that the groups of participants with and without those factors (experiences) had significantly different ideal L2 selves. Second, the experience of living abroad was not a significant differentiating factor for the ideal L2 self. Third, the results of the regression analysis suggested that school, home, and foreign media influences are significant contributors to the formation of the ideal L2 self. These factors may therefore subsume international travel and English cram school experiences. Discussion: By understanding the factors that contribute to the ideal L2 self, educators and policymakers can strive to establish a more effective environment to improve students' motivation to learn English.